Сказочные повести - Прокофьева Софья Леонидовна (Школьная библиотека, 2012)
Экземпляры: ООД, №6, №15 (20160323) / Инвентарный номер: 36731 / Цена: 118.80 / Авт.знак: П 80 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6